2015
DOI: 10.1016/j.tube.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Impaired CXCR1-dependent oxidative defence in active tuberculosis patients

Abstract: Much of the pronounced host inflammatory response that occurs in tuberculosis (TB) is related to failed immunity against the invading pathogen. The G-protein coupled receptors CXCR1 and CXCR2 are implicated in important signal transduction pathways in lung inflammatory responses. We investigated the expression and function of these receptors in a simple whole blood model from 24 patients with pulmonary TB and in subjects with latent TB infection (LTBI). Healthy controls were recruited from close contacts to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Comparison of CXCR1 expression on peripheral blood from TB patients shows that individuals with pulmonary TB have increased CXCR1, whereas latent TB patients have increased CXCR2 in whole blood (429). …”
Section: The Chemokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of CXCR1 expression on peripheral blood from TB patients shows that individuals with pulmonary TB have increased CXCR1, whereas latent TB patients have increased CXCR2 in whole blood (429). …”
Section: The Chemokinesmentioning
confidence: 99%
“…Moreover, increased CXCR1 correlates with impaired oxidative function in leukocytes suggesting a possible regulatory role for CXCR1 on oxidative stress (429). CXCR2 deficient mice infected intraperitoneally with M.avium have decreased neutrophil accumulation and increased bacterial burden (430).…”
Section: The Chemokinesmentioning
confidence: 99%
“…CXCL1 and 2 are known ligands of CXCR1 and 2 and individuals with TB have increased CXCR1 expression, while individuals with latent TB have increased CXCR2 expression. 22 The role of CXCL1 and 2 are not well understood in TB infection or disease, although they are mainly important in neutrophil recruitment in infections. Our data also suggest that altered levels of these chemokines could contribute to perturbations in the recruitment of neutrophils in la-tent TB in the context of LBMI.…”
Section: Discussionmentioning
confidence: 99%
“…GPCRs, such as CXCR1 and CXCR2, are important regulators in pulmonary diseases [52] . Previous research revealed that mycobacteria decrease epithelial cytokine production by manipulating these receptors [18] , and active TB patients were found to have increased CXCR1 expression [53] . CXCR2 is important in the pathology of a wide diversity of chronic pulmonary diseases, and the modulation of CXCR2 function is considered as a possible therapeutic strategy [54] .…”
Section: Discussionmentioning
confidence: 99%